The Impact of Locomotor Speed on the Human Metatarsophalangeal Joint Kinematics - Wang, Kunyang; Raychoudhury, Sivangi; Hu, Dan; Ren, Lei; Liu, Jing; Xiu, Haohua; Liang, Wei; Li, Bingqian; Wei, Guowu; Qian, Zhihui (Frontiers in Bioengineering and Biotechnology, 2021)
This paper aims to further our previous study to investigate the effect of speed on the three-dimensional (3D) kinematics of the human metatarsophalangeal (MP) joint during running on level ground. The 3D motion of the foot segments was captured by a twelve-camera motion analysis system, and the ground reaction forces and moments were recorded by using a six-force plate array. The relative motion data between the tarsometatarsi (hindfoot) and phalanges (forefoot) segments were used to determine the 3D orientation and position of the functional axis (FA) of the MP joint. The results show that the FA locates anterior to the anatomical axis (AA) with an average distance about 19% of the foot length (FL) across all running speeds, and is also 4.8% FL inferior to the AA during normal and fast run. Similar to walking, the FA shows a higher obliquity than the AA with an anteriorly inferior orientation across all the running speeds. This suggests that representing MP joint with the AA may mislead the calculation of joint moment/power and muscle moment arms not only in walking but also in running gait. Compared with previous study, we found that walking and running speeds have statistically significant effects on the position of the FA. The FA moves forwards toward a more anterior position with increased speed of walking and running. It transfers upwards in the superior direction with increasing speed of walking, but moves more towards the inferior position when the velocity increased further to running. Also, the orientation of FA in sagittal plane became more oblique towards the vertical direction as the speed increased. This may help in moderating the muscular effort, increase the muscle EMA, improve the locomotor performance and reduce the risks of injury. These results would contribute to understanding the in vivo biomechanical functioning of the human MP joint and also the propulsive function of the foot.